Comparison of Chinese and North American Tomographic Parameters and the Implications for Refractive Surgery Screening. Issue 2 (March 2020) - Boyd, Brennan M.; Bai, Ji; Borgstrom, Mark; Belin, Michael W.
Abstract : Purpose: The aim of this study was to determine whether there are significant clinical variations in the Belin/Ambrosio Enhanced Ectasia Display (BAD display) parameters between Chinese and North American eyes and whether any variations are related to differences in corneal diameter. Design: Retrospective observational study. Methods: Files were generated from patients seeking refractive surgical correction. Patients with previous surgery, evidence of corneal ectasia, or scans representing a non-normal cornea were excluded. Unpaired t tests were performed for all variables. Regression analyses were performed for all variables with respect to corneal diameter, and compared to evaluate the influence of corneal diameter between populations. Data were graphed as standard scores ( z scores) to compare different parameters. Results: 127 North American and 49 Chinese patients met study criteria. Statistically significant differences existed for corneal diameter ( P  < 0.01), anterior elevation at the thinnest point ( P  < 0.01), and Df ( P  < 0.01). In both populations, statistically significant correlations existed between corneal diameter and most indices, and most profoundly on pachymetric progression and final D. Regression slopes revealed a statistically significant difference for the influence of corneal diameter on ARTmax ( P  = 0.04) and was nearly significant for final D ( P  = 0.06). Conclusions: Corneal diameter had the greatest influence on pachymetric progression and final D, and more profoundly in the Chinese. This suggests that incorporating corneal diameter as an additional variable may make the BAD display more universally applicable. Also, the differences in anterior elevation parameters suggest that specific ethnic/geographic normative values may be beneficial for the BAD display.